Ena/VASP-EVH1 inhibition prevents chemotaxis and metastasis by blocking the EVH1–WAVE2 interaction - Matthias Müller; Matthias Barone; Maarten van Dinther; Kathrin Motzny; Jiang Ren; Jenny Eichhorst; Dominik Albat; Slim Chiha; Martin Lehmann; Rudolf Volkmer; Hartmut Oschkinat; Hans-Günther Schmalz; et al. (Proceedings of the National Academy of Sciences, 2025)
Cancer therapy would benefit from suppressing cancer cell motility in the process of metastasis. Such directed cell migration relies on the propulsive force established by the filamentous actin network within lamellipodia. Proteins of the Ena/VASP family and the WAVE regulatory complex orchestrate lamellar protrusions and therefore provide promising targets for pharmacological interventions. Here, we report a cross-talk between Ena/VASP proteins and WAVE2 that is important for cancer cell extravasation. Mutating the EVH1 domain recognition motif in WAVE2 abrogates chemotaxis of triple-negative MDA-MB-231 breast cancer cells and reduces their extravasation in a zebrafish model. In pilot experiments, orthotopic implantation of these cells into mice led to a reduction in macrometastasis, resulting in prolonged survival. Similarly, intervention by an Ena/VASP-EVH1 inhibitor also reduced metastasis in vivo. Our results suggest that pharmacological interference with the Ena/VASP–WAVE2 interaction may thus reduce metastasis.